Ethical reflection about medical errors and professional responsability (Saúde Ética & Justiça, 2002)
The authors discuss the doctor professional responsibility during the practice of profession. Takes in account, between other things, the relevance of the autonomy of will, related tothe expontaneous act and the impossibility of transfering moral responsibility, placing the medical doctor as the only agent of his/her own acts. Finally shows in a proper way the so called “medical malpactice” as a conclusion.